2016
DOI: 10.1095/biolreprod.115.135848
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Smoke Exposure Impairs the Long-Term Fertility of Female Offspring in a Murine Model1

Abstract: The theory of fetal origins of adult disease was first proposed in 1989, and in the decades since, a wide range of other diseases from obesity to asthma have been found to originate in early development. Because mammalian oocyte development begins in fetal life it has been suggested that environmental and lifestyle factors of the mother could directly impact the fertility of subsequent generations. Cigarette smoke is a known ovotoxicant in active smokers, yet disturbingly 13% of Australian and 12% of US women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…In animal models, experimental studies showed that exposure to maternal smoking, similar to study findings regarding maternal nutritional status, was related to negative reproductive health outcomes in the adult offspring, including indicators of sub-fertility, lower ovarian reserve, and increased oxidative stress [68][69][70]. Consistent with these findings, in a prior study of women, maternal smoking during pregnancy was associated with earlier menopausal timing in the offspring [41].…”
Section: Discussionsupporting
confidence: 55%
“…In animal models, experimental studies showed that exposure to maternal smoking, similar to study findings regarding maternal nutritional status, was related to negative reproductive health outcomes in the adult offspring, including indicators of sub-fertility, lower ovarian reserve, and increased oxidative stress [68][69][70]. Consistent with these findings, in a prior study of women, maternal smoking during pregnancy was associated with earlier menopausal timing in the offspring [41].…”
Section: Discussionsupporting
confidence: 55%
“…1). This has been shown for numerous substances: BPA [47], phthalates (DEHP [39, 41], DBP [38]), PAH [41, 96], cigarette smoke [65, 76, 77, 79, 82], pesticides [5154], dioxins [100], genistein [91], PCB [104]. Secondly, a decreased pool of primordial follicles (situation 5 in Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Effect of polymorphism of glutamate cysteine ligasePrenatal exposure to BaP induced POI. Deletion of glutamate cysteine ligase increased the sensitivity of these ovarian effectsCamlin et al, 2016 [82]Nasal exposure of pregnant mice to cigarette smoke for 12 weeks. Analysis of F1 ovary and oocyte qualityAbnormal proliferation of neonatal somatic cells,⇗ apoptosis, ⇘ follicles at birth and at the adult age.⇗ oxidative stress Human Data Progetto Menopausa Italia Study Group, 2003 [74]Cross-sectional study between 1997 and 1999.Inclusion of patients between ages 45 to 75 making a 1st consultation in a specialized center for menopause in ItalyNo significant association between the risk of POI and smokingChang et al, 2007 [72]Study of risk factors in 137 menopausal patients < 40 years, 281 between 40 and 4 years, and 1318 between 45 and 60 yearsSmoking ⇗ the idiopathic risk of POI: OR = 1.82 [1.03–3.23]Kinney et al, 2007 [110]Effect of cigarette smoking on antral follicle count and FSH in 188 patients aged 22 to 49 yearsChronic cigarette smoking is associated with higher rates of FSH β = 0.21, 95% CI = 0.04, 0.39, but there is no significant difference on the AFCStrohsnitter et al, 2008 [84]Epidemiological study on 4025 women.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant reduction in the number of retrievable good-quality GV oocytes was noted at 12 months (P < 0.0001), and this further decreased at 17 months (P < 0.0001).Collected GV oocytes were allowed to mature in vitro at 378C and 5% CO 2 for 16 hr until metaphase II (MII), in Minimum Essential Medium supplemented with fetal calf serum. The ploidy status of MII eggs was investigated using immunofluorescence confocal microscopy, as previously described by Camlin et al (2016). The spindles of MII eggs were collapsed with monastrol to spread chromosomes prior to fixation.…”
mentioning
confidence: 99%